A Computational Approach of Highly Secure Hash Algorithm for Color Image Steganography Using Edge Detection and Honey Encryption Algorithm - Dhanasekaran, K; Anandan, P; Manju, A (International Journal of Engineering and Technology, 2018)
Securing and transmitting data through images without being hacked is important in stegnography. Identification of the hidden data without the knowledge of appropriate algorithm is beyond bounds. In this paper we propose a highly secure algorithm for hiding data using advanced encryption algorithm, wherein the hidden data could be identified by canny edge detection and appropriate hash algorithm method. Color images are converted into grayscale images and edges are retrieved and honey encryption algorithm is used for encoding and decoding process. Simulated results in Matlab exhibits high security of the proposed method over other methods on comparison.Â Â